Television the critical view - Newcomb, Horace (Oxford University Press, 2000)
First published in 1976, Television: the critical view was the first book to offer a humanistic analysis of the history of media and television criticism. Now in its sixth edition, it points to the end of "the network era" and examines how the meaning of "television" continues to shift and change--Publisher.